Voice of editors: Population and economic growth - K. Sandy Kyaw (International Journal of Management, Economics and Social Sciences (IJMESS), 2019)
There has been debate amongst researchers and policy makers regarding how strong the correlation between population growth and economic growth is. At a time when several countries are encouraging policies to promote population growth, other countries are pursuing population stabilisation. For example, while countries such as Denmark, France, Japan and Singapore offer incentives aimed at encouraging births, policy makers aim for a reduction of population growth by curbing fertility rate in Burundi, Kenya, Niger and Rwanda, for example, via family planning programmes, to increase economic growth. The precise relationship between population and economic growth therefore requires further analysis.
Keywords: 330; Population; economic growth; aging